HUBUNGAN PERAN KELUARGA DENGAN TINGKAT KEBERHASILAN PENGOBATAN TBC PARU ANAK USIA SEKOLAH DI BALAI PENGOBATAN PENYAKIT PARU-PARU (BP.4) MEDAN - Rina Rahmadani Sidabutar (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACT Most of tuberculosis cases in children are caused by Mycobacterium tuberculosis bacteria around their houses. Children under 15 years old, including school-aged children 6 to 12 years of age, experience emotional disturbance which results in changes of the children behavior so that it will be very difficult to explain to a child about tuberculosis treatment procedure which takes about six until eight months. Therefore, it is necessary to find out how influential the family role is in the success rate of the treatment. Family has a very influential role in healing TB disease in children such as, consulting a doctor, accompanying the provision of medicines given through mouth, and also paying attention to the diet and nutrition of the children. The study was conducted with descriptive case study method. The sampling technique was accidental sampling with the sample size of 30 respondents out of 55 respondents. Data were collected by administering questionnaire and then were measured by the Rho Spearmen correlation test. The results showed a computerized statistical analysis identifying the relationship of family role which consisted of consulting a doctor, providing OAT through the mouth, and paying attention to diet and nutrition with TB treatment success in school-aged children with a significant level of 0.05. Contacting the doctor obtained a p value of 0.013 which shows a low relationship. Giving OAT through mouth obtained a p value of 0.026. This indicates a low relationship. Taking into account the diet and nutrition obtained p value of 0.021. This also shows a low relationship. Therefore, it is expected that students and nurses can improve the quality of nursing care to increase family participation in achieving the success of TB treatment in school-aged children.